Incomplete Antenatal Steroid Therapy Can Enhance Outcomes in Preterm Infants with Emergency Conditions - Sebnem Calkavur; Senem Alkan Ozdemir; Ruya Colak; Ezgi Yangin Ergon; Ferit Kulali; Tulin Gokmen Yildirim (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: We aimed to investigate the role of incomplete of antenatal steroid therapy by comparing with no and complete steroid exposure on mortality and morbidity in preterm infants.